SAT0363 Agreement Degree on the Adherence to Disease-Modifying Antirrheumatic Drugs (DMARD) Treatment in Rheumatoid Arthritis in Spain. Results of the Observar Study. (9th June 2015) - Castañeda, S.; Cantero, J.I.; Alegre, C.; Chamizo, E.; García, A.; García, M.E.; Garmendia, E.; Hernández, M.V.; Hidalgo, C.; Juan, A.; Martínez, J.A.; Martínez, V.; et al.
Abstract : Background: Adherence to treatment in rheumatoid arthritis (RA) is influenced by numerous factors. Although patients with RA are aware that compliance is important for disease control, there is evidence that they often drop out the prescribed use of synthetic DMARDs. Objectives: The OBSERVAR Study aims to confirm the lack of adherence to synthetic DMARDs in patients with RA and look for the main reasons for dropping out. Methods: Between July and August 2014, 18 Spanish consultant rheumatologists were asked, using a two-round Delphi process, to determine the degree of agreement with multiple causes of non-compliance. These reasons were selected by a systematic literature search in PubMed and Google Scholar, based on scientific publications. 66 reasons were selected, divided into 3 blocks, related to patients, to healthcare professionals and inherent to the DMARD treatment itself. The degree of agreement with each of these was identified on a scale from 1 to 9 (minimum and maximum agreement). The consistency of these agreements was determined by two criteria: based on the group mean, and based on simultaneous observance of mean and median ≥7, standard deviation and interquartile range ≤1.00, and coefficient of variation ≤0.25. Results: There was agreement with most of the statements selected (75.76%) and only one disagreement. Most frequent among the patient-related reasons were insufficient knowledge of the disease and importance of treatment adherence. The main reasons related to healthcare professionals were insufficient follow-up, lack of screening for non-compliant patients and lack of implementation of procedures aimed at improving adherence. With respect to treatment, general aspects were agreed such as the total number of pills or lack of reminder tools. When we applied the criterion of consistency of agreement, three reasons were highlighted (4.5%): not knowing what to do when the patient suffered an adverse event with the DMARD, lack of screening to detect non-compliant patients and lack of implementation of procedures to improve therapeutic compliance. Conclusions: The lack of strict adherence by patients in the treatment of RA with synthetic DMARDs is relatively common. Most of the reasons given for this have been confirmed in our study. The situation must be improved by: establishing objectives agreed with the patient; teaching them properly about the disease, treatment, expected side effects, the importance of adherence and its consequences; and by trying to identify potentially non-compliant patients early and subsequent continuous monitoring of their adherence. Acknowledgements: Roche Farma Spain Disclosure of Interest: None declared